Pivotal Impacts of Retrotransposon Based Invasive RNAs on Evolution - Habibi, Laleh; Salmani, Hamzeh (Frontiers in Microbiology, 2017)
RNAs have long been described as the mediators of gene expression; they play a vital role in the structure and function of cellular complexes. Although the role of RNAs in the prokaryotes is mainly confined to these basic functions, the effects of these molecules in regulating the gene expression and enzymatic activities have been discovered in eukaryotes. Recently, a high-resolution analysis of the DNA obtained from different organisms has revealed a fundamental impact of the RNAs in shaping the genomes, heterochromatin formation, and gene creation. Deep sequencing of the human genome revealed that about half of our DNA is comprised of repetitive sequences (remnants of transposable element movements) expanded mostly through RNA-mediated processes. ORF2 encoded by L1 retrotransposons is a cellular reverse transcriptase which is mainly responsible for RNA invasion of various transposable elements (L1s, Alus and, SVAs) and cellular mRNAs in to the genomic DNA. In addition to increasing retroelements copy number; genomic expansion in association with centromere, telomere and heterochromatin formation as well as pseudogene creation are the evolutionary consequences of this RNA-based activity. Threatening DNA integrity by disrupting the genes and forming excessive double strand breaks is another effect of this invasion. Therefore, repressive mechanisms have been evolved to control the activities of these invasive intracellular RNAs. All these mechanisms now have essential roles in the complex cellular functions. Therefore it can be concluded that without direct action of RNA networks in shaping the genome and in the development of different cellular mechanisms, the evolution of higher eukaryotes would not be possible.